The European initiative EHR4CR – Lessons learned for EHR implementations in Africa - Fritz, Fleur G.S.; Doods, Justin; Soto Rey, Inaki; Tilahun, Binyam; Dugas, Martin (Journal of Health Informatics in Africa, 2015)
Nowadays, more and more clinical data are documented in electronic health records and are thus available in digital form. With the aim of re-using these data for clinical research, a European consortium consisting of 35 partners from academia, clinics, pharmaceutical companies and subcontractors initiated the project "Electronic Health Records for Clinical Research" (EHR4CR). Three different services are envisaged to be supported for the design and implementation of clinical trials using a single platform: Clinical protocol feasibility, Patient identification and recruitment, Clinical trial execution and Serious adverse event reporting. Four different working groups focus on the following areas: Specifications and Business Model development, Technology Platform and Tools including semantic interoperability and data protection/security, Pilot Activities and Reference Site coordination as well as communication, dissemination and project management. It became apparent that one critical issue to reuse clinical data is the availability of structured, standardized data elements at the hospital sites. African countries that are currently implementing or planning to implement EHRs are strongly advised to make use of medical terminologies and data dictionaries when designing their systems. Medical documentation should be as structured as possible and interfaces be made available in order to reuse clinical data for reporting or research purposes. A common data inventory for medical documentation and health management reporting could be a starting point.